Tense and Aspect in the Languages of Europe : Tense and Aspect in the Languages of Europe. - Staff, Typology of Languages in Europe (Empirical Approaches to Language Typology EALT., 2000)
This volume puts the European tense-aspect systems in a consistent typological and diachronic perspective. The book advances our understanding of the dynamics of tense and aspect systems, how they develop over time, and how this is reflected in the rich patterns of synchronic variation and their areal distribution.